2019
DOI: 10.1103/physrevb.99.165124
|View full text |Cite
|
Sign up to set email alerts
|

Resonant inelastic x-ray scattering study of bond order and spin excitations in nickelate thin-film structures

Abstract: We used high-resolution resonant inelastic x-ray scattering (RIXS) at the Ni L3 edge to simultaneously investigate high-energy interband transitions characteristic of Ni-O bond ordering and low-energy collective excitations of the Ni spins in the rare-earth nickelates RNiO3 (R = Nd, Pr, La) with pseudocubic perovskite structure. With the support of calculations based on a doublecluster model we quantify bond order (BO) amplitudes for different thin films and heterostructures and discriminate short-range BO flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Most notably, the size of m LB /m SB is found to decrease at early time delays to a value below 1, followed by a gradual nanosecond recovery back to equilibrium. This suggests that the light excitation creates a state where the LB moment becomes smaller than the SB moment, which is inverse to the spin disproportionation found in the equilibrium low-energy spin model [18,20]. This state also differs from the equilibrium metallic state, as in this case no bond disproportionation between the two nickel sites is expected.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Most notably, the size of m LB /m SB is found to decrease at early time delays to a value below 1, followed by a gradual nanosecond recovery back to equilibrium. This suggests that the light excitation creates a state where the LB moment becomes smaller than the SB moment, which is inverse to the spin disproportionation found in the equilibrium low-energy spin model [18,20]. This state also differs from the equilibrium metallic state, as in this case no bond disproportionation between the two nickel sites is expected.…”
Section: Resultsmentioning
confidence: 86%
“…Powder neutrondiffraction measurements indicated a collinear AFM structure of the spins (↑↑↓↓) [13,14], while polarization-sensitive resonant soft x-ray scattering [15][16][17] and inelastic x-ray scattering [18] on thin films have found a noncollinear spin spiral structure (↑→↓←). Recent x-ray scattering studies on thin films have also found the spins to have a canting angle less than 90°, with a collinear structure emerging in the limit of monolayer thickness [19,20].…”
Section: (Lb) and D 8 L 2 (Sb)mentioning
confidence: 99%
“…Figure 2A shows the XAS measurements taken in the standard experimental setup at the Ni-L edge for both pristine and reduced pieces of the same sample. For the pristine piece, we observe the well-known double-peak structure at the Ni-L 3 edge, indicative of charge fluctuations in the metallic phase [23][24][25]. Upon topotactical reduction, both the Ni-L 2 and L 3 edges shift towards lower energies, suggesting the transition from a Ni 3+ oxidation state towards Ni 2+ and Ni 1+ [11].…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 75%
“…By contrast, for the subsequent members, the TMI increases from PrNiO3 (TMI = 130 K) to LuNiO3 (TMI =599 K) and the TN shows a monotonic variation. The nature of the electronic transition has been systematically studied by spectroscopic and diffraction techniques [19][20][21][22][23] . Charge disproportionation 15,[24][25][26][27][28] and charge ordering 29,30 are the main mechanisms proposed to explain charge localization in the insulating regime, as the smaller rare-earth derivatives (R= Y, Dy  Lu) display a concomitant transition from the more regular perovskite high-temperature orthorhombic (Pbnm) structure to the low-temperature insulating monoclinic (P21/n) structure, which shows an alternating breathing-like distortion of the NiO6 octahedral arrangement.…”
Section: Introductionmentioning
confidence: 99%